Understanding the role of childhood abuse and neglect as a cause and consequence of substance abuse: the German CANSAS network - Schäfer, Ingo; Barnow, Sven (European journal of psychotraumatology, 2017)
Background: Substance use disorders (SUD) belong to the most frequent behavioural consequences of childhood abuse and neglect (CAN). If parents are concerned, SUD are also an important risk factor for CAN. The relationship between CAN and SUD remains poorly understood. There is a need of adequate treatments for SUD patients suffering from the consequences of CAN, as well as for approaches to prevent CAN by parents with SUD. Objective: To describe the aims and the structure of a German research network on relationships between CAN and SUD (CANSAS network). Method: Descriptive overview of the aims, and the different project clusters of the network. Results: The aims of the CANSAS network are: (1) to examine relationships between SUD and CAN; (2) to examine the effects of an evidence-based treatment for SUD patients with posttraumatic disorders; and (3) to provide SUD services with tools to diagnose CAN, and to assess the risk of maltreatment among parents with SUD. The aims of the network are addressed by six projects in three different project clusters (mediators and risk factors, evidence-based treatment, and improvement of services). Conclusions: It is expected that the CANSAS network will advance the understanding of relationships between early adversity and substance use disorders. It will bring forward the discussion about promising treatments for SUD patients with experiences of CAN. Finally it will provide services with measures to identify patients with CAN, and with tools to break the trans-generational cycle of adversity.
Gesehen am 27.09.2017